(untitled) (Scripta : English Department Journal, 2026)
This study aims to analyze English teachers’ perceptions of implementing deep learning within Project-Based Learning (PjBL) at Muhammadiyah educational institutions in Pagaralam. The rapid development of 21st-century education demands learning approaches that promote critical thinking, creativity, collaboration, and meaningful understanding. Deep learning, combined with PjBL, is considered an effective strategy to achieve these goals. This research employed a qualitative descriptive design involving 17 English teachers from SMA and SMK Muhammadiyah Pagaralam as participants. Data were collected through semi-structured interviews and questionnaires and analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that most teachers have a basic understanding of deep learning, perceiving it as a learning approach that emphasizes conceptual understanding and critical thinking rather than memorization. Teachers also demonstrate positive perceptions of PjBL, recognizing its role in enhancing student engagement and real-life application of knowledge. However, the implementation of deep learning within PjBL is not yet optimal, as students often focus more on completing projects than achieving deep understanding. Supporting factors include school facilities, teacher collaboration, and institutional support, while inhibiting factors include limited instructional time, students’ readiness, and lack of training. This study concludes that although teachers show positive perceptions, effective implementation requires continuous professional development and stronger institutional support.